Victorians and modern Greece
1 online resource.
Keywords: "Victorians and Modern Greece examines the representation of nineteenth-century Greece in British magazines, fiction, poetry, and travel writing, revealing the popular reception of the modern nation in the Victorian period. Reflecting upon the tensions - ancient and modern, oriental and European, primitive and developed - emerging from Victorian texts on Modern Greece, the twelve essays in this volume analyse these texts and their role in reconceptualising the national identity and culture of Britain and Greece through their encounter with each other. Featuring writers such as Mary Shelley, Christopher Wordsworth, William Thackeray, Theodore Bent, Isabella Fyvie Mayo, Oscar Wilde, and Vernon Lee, as well as anonymous authors publishing in popular periodicals, and a broad range of topics from travel and fashion to political crises and the pervasive appeal of ruins, this book tells the story of Modern Greece from British perspectives, at a time when Greece was struggling to achieve self-definition among conflicting geopolitical interests. Victorians and Modern Greece also introduces Victorian studies to minor or marginal voices and narratives which addressed worldly concerns and Britain's global affiliations. With its comparative perspective, this book will be of interest to scholars and students of both Victorian literature and culture and of the culture and history of Modern Greece"--